Congenital Syphilis - Velásquez-Vásquez, Carlos (2018)
With the large development of the global fight against human immunodeficiency virus, congenital syphilis (CS) has remained a silent epidemic that has seen increasing mortality and morbidity indicators fetal / neonatal. Epidemiologically the highest rates of CS are in countries where the health system is not the most suitable for the care of the mother and child from there to talk to the CS rate is a negative indicator of health systems. Some conditions, such as the difficulty of diagnosis and changes in criteria for determination, not allowed to have reliable information about its impact, although it is clear that third world countries especially sub-Saharan Africa are most affected by this. WHO estimates that each year is responsible for 460,000 abortions or stillbirths, 270 000 cases of congenital syphilis and the birth of 270 000 premature or low birth weight.The SC can manifest in fetal death and spontaneous abortion after the first trimester of pregnancy, or stillbirth by 30 to 40%, or can culminate in the birth of a premature infant with obvious clinical signs of infection, or birth completely asymptomatic. Clinical presentation will depend on the degree of organ involvement by the immune response to Treponema from the fetal stage. The treatment of choice is penicillin, but the best way to eliminate the diagnosis and treatment of maternal syphilis during pregnancy